2019
DOI: 10.3390/app9153163
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Various Factors Affected TID Tolerance in FinFET and Nanowire FET

Abstract: Analysis of the radiation effects in a device is of great importance. The gate all around (GAA) structure that contributes to device scaling not only solves the short channel effects (SCE) problem but also makes the device more resistant in radiation environments. In this article, the total ionizing dose (TID) simulation of nanowire FET (NW) and FinFET was performed. Both these devices were compared and analyzed in terms of the shift of threshold voltage (V T ). The channel insulator was composed of two materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…In particular, it is well-fixed at increased temperatures of 380 K and 400 K, and, moreover, negatively influences the curvature of transistor transmission characteristics. Obtained results are wellcorrelated with the results obtained by us and other authors in case of SiNW FETs [1-3, 7, 14-16] and FinFETs [3,4,7]. It should be noted that direct studies of the structure and phase states, electrophysical properties of thermal-stable bimetallic film alloys have been obtained by theauthors in [17][18][19][20].…”
Section: Simulation and Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…In particular, it is well-fixed at increased temperatures of 380 K and 400 K, and, moreover, negatively influences the curvature of transistor transmission characteristics. Obtained results are wellcorrelated with the results obtained by us and other authors in case of SiNW FETs [1-3, 7, 14-16] and FinFETs [3,4,7]. It should be noted that direct studies of the structure and phase states, electrophysical properties of thermal-stable bimetallic film alloys have been obtained by theauthors in [17][18][19][20].…”
Section: Simulation and Resultssupporting
confidence: 85%
“…Among them, except the possibility of further nanoscale procedure, GAA NWFETs have excellent gate controlling, short-channel effects (SCEs) stability [5,6], etc. As an example, in paper [7], structural models of a 5-channel GAA NWFET were designed and their performance characteristics were compared depending on the operating conditions. The authors of [8] showed that NW-channel transistors have better operating characteristics than FinFETs, their concentration and other dependencies were analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Various models (trap-detrap, mobility, etc.) were used to improve the accuracy of the simulation [11][12][13][14]. After irradiation at 1 rad/s, when the desired amount of radiation stress was applied, the gate voltage was swept to 0 V again.…”
Section: Methods Of Analyzing Tid Effectsmentioning
confidence: 99%
“…The results of numerical simulation by Silvaco TCAD [1] of 3D FET-transistors with five n-type of conductivity Si-nanowires (n-SiNW FET's) 5-channels, based on Gate-all-around (GAA) structure are presented. Among them except the possibility of further nanoscale procedure, GAA n-SiNW FET's have an excellent gate controlling, short-channel effects (SCE's) stability [2][3][4][5][6], etc. It is demonstrated their distinct electrical characteristics, in particular there were obtained the valid values of threshold voltage V t , leakage current I off and I on /I off coefficient, subthreshold scattering SS and drain induced barrier lowering (DIBL).…”
Section: Ukrainementioning
confidence: 99%